Throughput Analysis on a Multi-state Manufacturing System by Considering Availability - Nabila Yuraisyah Salsabila; Nurhadi Siswanto; Erwin Widodo; Oryza Akbar Rochmadhan (Jurnal Teknik Industri, 2019)
Manufacturing technology becomes more complex as customer demand increases. Most manufacturing companies consist of multi-state manufacturing networks. Therefore, the reliability and availability parameters become an important issue to satisfy customer demand. Unavailability can result in reducing throughput because of decreasing operational production time. To resolve this problem, the buffer inventory can minimize the occurrence of material starving and production blocking during the equipment downtime. This paper will focus on experimenting with buffer inventory levels and the capacity of a multi-state manufacturing network to increase the production throughput on a company that has 70,000 tons per year of capacity. However, due to the unavailability problem, the existing system capacity decreases to 62,175 tons per year. The simulation model is used to improve throughput by modeling the failure interruption and the buffer inventory logics during the production process.